2020
DOI: 10.1096/fasebj.2020.34.s1.06577
|View full text |Cite
|
Sign up to set email alerts
|

The Toxic Effect of Environmental Cadmium on Visceral Adipose Tissue

Abstract: Cadmium is an environmental toxin strongly associated with the development of cancer, kidney and liver disease, and bone demineralization. Whether cadmium causes obesity in humans remains a subject of controversy in the literature. An NHANES study that examined the effect of various toxic metals on central obesity demonstrated a decrease in the BMI of subjects exposed to cadmium. The purpose of this study is to examine the effect of cadmium on visceral adipose tissue (VAT), the potential for chelation to rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Our results showed that Cd exposure caused a significant decrease in rats’ body weight. The reduction of the body weight agrees with former studies that recorded Cd exposure caused a downregulation in the body weight of murine ( Kawakami et al, 2010 ; Prabhu et al, 2020 ). The reduction of the body weight in the Cd-T group is suggestive of either losing adipocytes or dysregulated adipogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that Cd exposure caused a significant decrease in rats’ body weight. The reduction of the body weight agrees with former studies that recorded Cd exposure caused a downregulation in the body weight of murine ( Kawakami et al, 2010 ; Prabhu et al, 2020 ). The reduction of the body weight in the Cd-T group is suggestive of either losing adipocytes or dysregulated adipogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Despite some existing contradictions, the experimental data provide insight into dose-dependent effects of heavy metals on adipogenesis. It is proposed that the effects of heavy metal exposure on adipose tissue is biphasic ( Figure 1 ), varying from increased adipogenesis at low-dose exposure to inhibition of adipose tissue differentiation at higher doses, as demonstrated for Hg 21 , 22 , Cd 55 , 56 , 58 , 59 , and As 41 . However, direct dose-response analysis was performed only for the latter 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, a study originating from Mexico City demonstrated an inverse association between maternal urinary Cd levels and abdominal and peripheric adiposity 57 . An experimental in vivo study demonstrated that administration of 100 ppm CdCl 2 in drinking water to ICR mice for 8 weeks resulted in a significant decrease in adipocyte size but that Cd chelation using dimercaptosuccinic acid (DMSA) ameliorated this effect 58 . This effect may be at least partially mediated by the earlier demonstrated Cd-induced (3 μM) inhibition of adipogenesis and a dose-dependent decrease in C/EBPα and PPARγ protein expression in 3T3-L1 preadipocytes 59 .…”
Section: Adipotropic Effects Of Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…More exploration was done by the same team, to study the effect of acute Cd exposure in MT-null mice and found that, adipocytes size was significantly reduced (Kawakami et al 2013). In agreement with these results, a recent study reported that mice exposed to Cd for 8 weeks exhibited a significant reduction in both body weight and adipocytes size (Prabhu et al 2020). However, an earlier study that examined the Cd effect on AT using a rat model, reported no changes in both body weight and adipocyte size (Ficková et al 2003).…”
Section: Cadmium and Adipose Tissue Dysfunctionmentioning
confidence: 59%